An Assessment of Drawing Age in Pre-School Children Using ’Draw-A-Man’ Test - Raja, S; John, BM (Journal of Nepal Paediatric Society, 2014)
Introduction: Goodenough-Harris ‘Draw-a-Man’ Test has been traditionally used as a simple tool to measure mental development in a child. There have very few studies looking at utility of ‘Draw a man’ test in the Indian subcontinent in the recent past. We carried out an assessment of correlation of drawing age with chronological age in pre-school children by the ‘Draw- a- man test’ and looked for any associations with respect to a deviation (delay or advancement) in the calculated drawing age. Materials and Methods: A cross-sectional descriptive study was conducted on 100 neurologically normal pre-school children between 36 to 72 months. The data was then analyzed with Pearson correlation and Chi square test on SPSS version 14.0 Result: There was a low positive correlation between drawing age and chronological age (Pearson correlation: r=+0.31, p=0.002).There were more boys (p=0.004) and more children with prematurity (p=0.012) in the group with low or equal drawing age compared to chronological age. Conclusion: In view of the low positive correlation found in our study, further studies with a larger sample need to be conducted to establish the ‘Draw-a-man’ test as a screening tool for mental age assessment in our subcontinent. We did find a significant association of deviation of drawing age from chronological age with respect to gender and prematurity. DOI: http://dx.doi.org/10.3126/jnps.v34i1.9299 J Nepal Paediatr Soc 2014;34(1):14-17